An Overview of Amish Mortalities at a Level I Trauma Center. Issue 3 (March 2022) - Morgan, Madison E.; Brown, Catherine Ting; Whitney, Larissa; Bonneville, Kelly; Perea, Lindsey L.
Background: The Amish population is a unique subset of patients that may require a specialized approach due to their lifestyle differences compared to the general population. With this reasoning, Amish mortalities may differ from typical trauma mortality patterns. We sought to provide an overview of Amish mortalities and hypothesized that there would be differences in injury patterns between mortalities and survivors. Methods: All Amish trauma patients who presented and were captured by the trauma registry at our Level I trauma center over 20 years (1/2000-2004/2020) were analyzed. A retrospective chart review was subsequently performed. Patients who died were of interest to this study. Demographic and clinical variables were analyzed for the mortalities. Mortalities were then compared to Amish patients who survived. Results: There were 1827 Amish trauma patients during the study period and, of these, 32 (1.75%) were mortalities. The top 3 mechanisms of injury leading to mortality were falls (34.4%), pedestrian struck (21.9%), and farming accidents (15.6%). Pediatric (age ≤ 14y) (25%) and geriatric (age ≥ 65y) (28.1%) had the highest percentage of mortalities. Mortalities in the Amish population were significantly older (mean age: 39 years vs 27 years, P = .003) and had significantly higher ISS (mean ISS: 29 vs 10, P < .001) compared to Amish patients who survived. Discussion: The majority of mortalities occurred in the pediatric and geriatric age groups and were falls. Further intervention and outreach in the Amish population should be done to highlight this particular cause of mortality. Level of Evidence: Level III, epidemiological.